HEC-RAS 2D modeling for flood inundation mapping: a case study of the Krishna River Basin. Issue 4 (6th April 2023) - Vashist, Komal; Singh, K. K.
Abstract: Floods are catastrophic natural disasters that cause a substantial toll on human lives, infrastructure, and the economy. Structural and non-structural measures are developed for planning flood mitigation strategies. Flood inundation mapping is valuable information for decision-makers and authorities to develop flood mitigation strategies and resource allocation. This study uses the HEC-RAS 2D model for flood inundation mapping in the Krishna River Basin. Digital elevation models (DEMs) of 12.5 and 30 m resolutions were used to model the inundation map. The study also investigated the effect of change in upstream boundary data on the inundated area. The simulated results with 12.5 m resolution DEM are found in good agreement with the validation data and conform to the inundated areas with the available reports. This study proves the 2D capabilities of HEC-RAS and helps the experts with better management practices. HIGHLIGHTS: Flood inundation mapping was performed on the Krishna River Basin using the HEC-RAS 2D model. Digital elevation models (DEMs) of 12.5 m resolution and 30 m resolution were incorporated to perform the inundation mapping. The study investigated the influence of varying the upstream boundary data on the inundated area. The simulated results with 12.5 m resolution DEM give a good agreement with the data available for the validation. Graphical Abstract